IMPLEMENTATION OF BUSINESS MANAGEMENT FOR SUSTAINABLE DEVELOPMENT IN THE PHARMACEUTICAL INDUSTRY (CIPEEX, 2022)
&NBSP;IT WAS FROM THE MID-1980S THAT SUSTAINABLE DEVELOPMENT BEGAN. FROM THE CREATION OF AGENDA 21 IN ECO-92 THE SUBJECT BECAME AN AGENDA IN THE CORPORATE WORLD. HOWEVER, THE THEME NEEDS CONSTANT DISCUSSIONS AND ANALYSIS, AS THE RESULTS ARE OBTAINED IN THE LONG TERM. THE SEARCH FOR BALANCE REQUIRES CONNECTION BETWEEN THE PARTIES INVOLVED: COMPANY, STATE AND COMMUNITY. IT IS ARGUED THAT IN THE CORPORATE ENVIRONMENT IT IS NECESSARY TO INVEST IN THE IMPLEMENTATION OF PRACTICES THAT RESULT IN THE MINIMIZATION OF THE IMPACTS CAUSED BY INDUSTRIALIZATION AND THAT PUT AT RISK ENVIRONMENTAL SERVICES. THIS CAN BE ACHIEVED WITH A SUSTAINABLE BUSINESS MANAGEMENT MODEL, BASED ON THE CONCEPT OF CIRCULAR ECONOMY, REPRESENTING AN ALTERNATIVE PATH TO ACHIEVING THE SUSTAINABLE DEVELOPMENT GOALS (SDGS). BEING THE RELEVANT THEME FOR THE CONSERVATION AND PRESERVATION OF NATURAL RESOURCES, THE IMPLEMENTATION OF A WASTE MANAGEMENT WITH FULL USE OF MATERIALS, MEETING IN AN INTEGRATED WAY THE LEGAL PARAMETERS DEFINED BY THE COMPETENT AGENCIES, AND SOCIO-ENVIRONMENTAL GAINS. THE 5RS METHODOLOGY SOLIDIFIES THE PROPOSED MODEL, ENTITLED "ZERO LANDFILL", MAINTAINING THE 100% INDEX OF WASTE SENT FOR RECYCLING OR RECOVERY AND INCREASES THE REVENUE FOR INVESTMENTS IN THE LOCAL COMMUNITY. THE ENVIRONMENTAL STRATEGY SHOULD CONTRIBUTE TO ECONOMIC AND SOCIAL DEVELOPMENT THROUGH A BUSINESS MANAGEMENT FOR SUSTAINABLE DEVELOPMENT GENERATING CONSISTENT BENEFITS. THE REDUCTION OF TOTAL WASTE BY 52%, INCREASE OF PROFIT AND SOCIO-ENVIRONMENTAL GAINS IN A PHARMACEUTICAL INDUSTRY, CHALLENGE EXISTING CONCEPTS IN THE LINEAR MANAGEMENT MODEL, INDICATING RELEVANCE OF THE CIRCULAR MANAGEMENT MODEL IMPLEMENTED AND THE POSSIBILITY OF REPLICATION IN OTHER PRODUCTION PROCESSES.